Buy now, pain later? Over-indebtedness of young individuals* - Damar-Blanken, Duygu (Taylor and Francis, 2025)
This chapter examines the newest type of small and short-term credit, namely Buy Now, Pay Later (BNPL) offers. BNPL is especially popular in e-commerce due to the convenient procedures of access. Yet it also poses a high risk of over-indebtedness, especially for young persons who are specifically susceptible to impulse buying and who, at least to a certain extent, lack financial literacy. The New Consumer Credit Directive of the European Union takes a huge step in financial consumer protection by extending its scope to small and short-term credit agreements, that is, also to BNPL-credit. However, the safeguards put in place by the new Directive might prove insufficient due to the business model underlying BNPL-credit. This chapter argues that, in order to achieve responsible lending practice and improve the financial literacy of young persons, an additional monitoring feature is necessary. © 2026 selection and editorial matter, Duygu Damar-Blanken and Michelle Kelly-Louw; individual chapters, the contributors.
Keywords: Finance; Business Models; Consumer Credits; E- Commerces; European Union; Financial Literacy; Impulse Buying; Consumer Protection